На кордоні зі Степом: південна група городищ скіфського часу в Дніпро-Донецькому Лісостепу - Крютченко, О.О. (Археологія і давня історія України, 2018)
Стаття присвячена дослідженню системи поселенських структур та поховальних комплексів
розташованих вздовж Муравського шляху, на кордоні зі степом. Мова йде про п'ять городищ, майже
шістдесят селищ, три могильники та два пункти з окремими впускними похованнями, що компактно розташовані на півдні Лісостепу та належать сіверськодонецькій групі пам'яток скіфської доби. The structure of the fortified settlements enlargemented
on the territory of the Dnipro-Don foreststeppe,
starting from the middle-second half of the
VI century BC. According to the results of the investigation
of the Bilsk hillfort, the Perekipsky shaft in the
Kharkiv region and settlements along the Muravsky
path, we suggest that the functions of these fortifications
were much wider than the protection of the inhabitants
of the surrounding settlements. In this article
we summarize the results of the investigation of the
settlement group and burial fields that are located on the border of the steppe.